2021
DOI: 10.1155/2021/5521715
|View full text |Cite
|
Sign up to set email alerts
|

Key Markers and Epigenetic Modifications of Dental-Derived Mesenchymal Stromal Cells

Abstract: As a novel research hotspot in tissue regeneration, dental-derived mesenchymal stromal cells (MSCs) are famous for their accessibility, multipotent differentiation ability, and high proliferation. However, cellular heterogeneity is a major obstacle to the clinical application of dental-derived MSCs. Here, we reviewed the heterogeneity of dental-derived MSCs firstly and then discussed the key markers and epigenetic modifications related to the proliferation, differentiation, immunomodulation, and aging of denta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 249 publications
(238 reference statements)
0
2
0
Order By: Relevance
“…It is now understood that DSCs can be readily obtained from tissues originating from the oral region [4]. To date, numerous different types of human DSCs have been identified and named according to their origin, including dental pulp stem cells (DPSCs) [5], stem cells from human exfoliated deciduous teeth (SHED) [6], stem cells from apical papilla (SCAPs) [7], periodontal ligament stem cells (PDLSCs) [8], dental follicle cells (DFCs) [9], and gingival mesenchymal stem cells (GMSCs) [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is now understood that DSCs can be readily obtained from tissues originating from the oral region [4]. To date, numerous different types of human DSCs have been identified and named according to their origin, including dental pulp stem cells (DPSCs) [5], stem cells from human exfoliated deciduous teeth (SHED) [6], stem cells from apical papilla (SCAPs) [7], periodontal ligament stem cells (PDLSCs) [8], dental follicle cells (DFCs) [9], and gingival mesenchymal stem cells (GMSCs) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Current identified DSCs are dental pulp stem cells (DPSCs) (1,2), stem cells from human exfoliated deciduous teeth (SHED) (3), periodontal ligament stem cells (PDLSCs) (4), dental follicle precursor cells (DFPCs) (5), stem cells from apical papilla (SCAP) (6), gingival-derived MSCs (GMSCs) (7), and alveolar bone marrow-derived MSCs (ABMSCs) (8,9). In vitro identification demonstrated that DSCs positively expressed MSC-related markers, including CD13, CD29, CD44, CD59, CD73, CD90, CD105, CD146, and STRO-1; while negatively expressed hematopoietic markers, such as CD14, CD31, CD34, and CD45 (10)(11)(12). The key pluripotency markers (Oct4, Sox2, and Nanog) that are involved in maintaining the undifferentiated state were also expressed in DSCs with different levels (13).…”
Section: Introductionmentioning
confidence: 99%